2007
DOI: 10.1159/000101756
|View full text |Cite
|
Sign up to set email alerts
|

Community Engagement in Genetic Research: Results of the First Public Consultation for the Quebec CARTaGENE Project

Abstract: Objective: This paper presents the results of the first public consultation for the creation of a large-scale genetic database, the Quebec CARTaGENE project. A consultation has been undertaken in order to gauge whether the general public is receptive to the project. An integral part of the approach of the researchers is to establish a dialogue with the public. Methods: Two independent expert groups have carried out qualitative and quantitative studies measuring knowledge of and interest in genetics, incentives… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
105
2
1

Year Published

2008
2008
2015
2015

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 89 publications
(115 citation statements)
references
References 30 publications
7
105
2
1
Order By: Relevance
“…Consistent with prior studies, principal concerns of SDMs were that a genetic sample might be diverted for inappropriate purposes, or would lead to insurance and employment discrimination. 14,18,23,27 However, in contrast to these previous investigations, was our finding that SDMs perceived the risk associated with gene variation research largely as the risk associated with acquiring the genetic sample (i.e., whether or not sample acquisition involved an invasive procedure), as opposed to characteristics of the sample itself. This altered frame of reference might reflect the acuteness of the illness of their loved ones, as well as the number and nature of medical interventions these individuals had recently undergone.…”
Section: Discussioncontrasting
confidence: 96%
See 2 more Smart Citations
“…Consistent with prior studies, principal concerns of SDMs were that a genetic sample might be diverted for inappropriate purposes, or would lead to insurance and employment discrimination. 14,18,23,27 However, in contrast to these previous investigations, was our finding that SDMs perceived the risk associated with gene variation research largely as the risk associated with acquiring the genetic sample (i.e., whether or not sample acquisition involved an invasive procedure), as opposed to characteristics of the sample itself. This altered frame of reference might reflect the acuteness of the illness of their loved ones, as well as the number and nature of medical interventions these individuals had recently undergone.…”
Section: Discussioncontrasting
confidence: 96%
“…14,16,21,22 We found that although SDMs expressed the opinion that either they or their loved ones would be interested in learning individual study results, they requested recontact and reconsent to permit future use. When it was discussed that it would be necessary to archive samples in a nonanonymous fashion so as to enable these requests, SDMs opted for anonymity, foregoing the opportunity to receive study results.…”
Section: Discussionmentioning
confidence: 90%
See 1 more Smart Citation
“…The survey instrument was developed by the study team drawing on previous research and a review of the literature, 7,22,33,38,39 and was pretested with 10 eligible respondents (who were excluded from the final sample). It included a non-experimental component consisting of 22 items: (i) three demographic questions about the respondent's primary role in research, professional training and gender, (ii) seven practice questions about barriers to care in the respondent's jurisdiction, and the role of the respondent's research team in providing information to participants, and (iii) 12 attitude questions about the respondent's perceived responsibilities toward research participants, beliefs about the potential for harm from provisional scientific information, and beliefs about the role of genes in ASD or CF.…”
Section: Survey Instrumentmentioning
confidence: 99%
“…7,8 Invoking the principle of beneficence, many argue further that it is in participants' best interest to learn this information; 4 the common suggestion that results should meet some test of clinical significance (varying from clinical through personal utility) [4][5][6][7][8][9][10][11][12][13][14][15][16] to warrant reporting supports this point. Proponents find confirmation for their position in empiric research with research participants, many of whom believe that such information is owed 3,9,[17][18][19][20][21][22][23][24] and/or will have meaning in their lives. 19,23,[25][26][27][28] Others contend that although the principles of respect for persons, reciprocity, and beneficence should be upheld in the context of research, they may neither be well served if results are disclosed nor denied if they are not disclosed.…”
Section: Introductionmentioning
confidence: 99%